Assessing graduates’ attributes and job performance for program curriculum enhancement - Albay, Eduard M.; Aquino, Ronald L.; Alambra, Ralph Vincent E.; Eisma, Delia V.; Quiambao, Raquel D. (International Journal of Evaluation and Research in Education (IJERE), 2024)
Graduate tracer studies are essential for higher education institutions (HEIs) as valuable information can be uncovered and derived that is useful for curriculum development, revision, or enhancement. This descriptive research study, using a questionnaire as the main data-gathering tool, determined the job attributes and job performance of the Bachelor of Science (BS) Mathematics graduates from 2013 to 2017 from a state university in the Philippines. Results revealed that the graduates were currently employed in various positions in both private and government institutions, with either permanent or contractual status. The graduates identified skills in mathematics, communication, computer, human relations, entrepreneurship, problem- solving, and critical thinking as vital in performing their duties and obligations in the workplace. Overall, the graduates’ job performance is outstanding. Based on the findings, suggestions to improve the BS Mathematics curriculum of the concerned HEIs were discussed to make it more relevant, responsive, adaptive, and inclusive.